The Role of Lecturers in Character Development Through Aswaja-Based Learning at STIT Hasyim Asy’ari Padangsidimpuan - Endayana, Bestari; Tania , Rikha; Serlinda, Serlinda (Journal of Educational Research and Practice, 2023)
This research explores the role of lecturers in developing Aswaja character through Aswaja learning at STIT Hasyim Asy’ari Padangsidimpuan. The use of Aswaja learning significantly impacts the development of characters in line with Islamic teachings. It provides an opportunity for students to understand Islam deeply, encompassing the principles of Ahlussunnah wal Jamaah, beliefs, and spiritual practices. Furthermore, Aswaja learning shapes positive moral vaues such as honesty, patience, justice, and compassion, serving as the foundation for Islamic character. The study emphasizes the importance of Aswaja learning in encouraging students to apply the learned values in their daily lives, makin Islamic character not just a theorical concept but an integral part of students’ behavior and decisions. Lecturers play a central role as role models in implementing Aswaja values, not only conveying religious information but also serving as concrete examples in applying this values. The holistic approach of Aswaja learning contributes not only to religious knowledge but also plays a crucial role in shaping a strong Islamic character in accordance with Islamic teachings. The Implementation faces challenges such as resistance and resource needs, requiring appropriate strategies, campus-wide involvement, and efforts to enhance human resources’ quality. STIT Hasyim Asy’ari Padangsidimpuan strives not only to provide Islamic higher education but actively shapes individuals with a robust character based on Aswaja values. In conclusion, this research sheds light on the pivotal role of lecturers and the significance of Aswaja learning in character development within the context of Islamic higher education.